Consumer Characteristics Of Micro, Small And Medium Enterprises (MSMEs) Buah Baru Online - Setiyani, Rahmawati; Edi Waluyo, Sugeng; Rahmadhani, Istining (LPPM Universitas Duta Bangsa Surakarta, 2024)
Micro, Small and Medium Enterprises (MSMEs) Buah Baru Online is one of the MSMEs that focuses on marketing fruits online. Marketing is carried out by MSMEs Buah Baru Online through website and social media such as Tiktik and WhatsApp. The aim of this research is to determine the characteristics of MSMEs Buah Baru Online consumers. The population in this research is all consumers of MSMEs Buah Baru Online. The sample in this research was consumers of MSMEs Buah Baru Online who had shopped at MSMEs Buah Baru online and were at least 18 years old. The basic method used in this research is to use descriptive analysis obtained from diagram analysis. Consumer charateristics of MSMEs Buah Baru Online are dominated by female consumers, age range 35-44 years old, with employee work and income of more than IDR 3.000.001 per month.